Good Teacher, Qualified Teacher, and Professional Teacher: Facing the 21st Century Global Changes - Pratiwi Tri Utami; Nurul Hasanah (Ahmad Dahlan Journal of English Studies, 2020)
The role of teacher cannot be separated in teaching and learning process. In fact, teacher hold an important role to improve the quality of education especially for facing 21st century global change. In this globalization era, it drives to the increasing need of knowledge and communication to survive. It forces the teacher to take the responsibility to fulfill what the students need since the teachers meet directly to the student to meet the 21st century skills. Thus, teacher quality may strongly influence and affect the educational quality. Discussing about teacher quality, some terms will come out; good teacher, qualified teacher, and professional teacher. In developing country, those kinds of teachers are very needed to improve the quality of education. In fact, it is very rare that a teacher has three of them. Despite of that, it becomes a confusion regarding to those terms. Are they different? And how can they different? In this article, it will be discussed about the differences of good teacher, qualified teacher, and professional teacher. After defining the differences of them, we can see which one is the appropriate to be improved for developing country where in this research is for Indonesia case. In conclusion, referring to some matters in Indonesia, professional teacher should be concerned by the government to achieve the good quality in education.